Preclinical and clinical evidence for the treatment of non-alcoholic fatty liver disease with soybean: A systematic review and meta-analysis - Li, Yubing; Deng, Xinyu; Guo, Xiaochuan; Zhang, Fangling; Wu, Hefei; Qin, Xuhua; Ma, Xiao (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a prevalent public health issue involving the accumulation of triglycerides in hepatocytes, which is generally considered to be an early lesion of liver fibrosis and cirrhosis. Thus, the development of treatments for NAFLD is urgently needed. The study aims to explore the preclinical and clinical evidence of soybean to alleviate NAFLD. Three relevant databases were retrieved: Web of Science, PubMed, and Embase. The time range was from January 2002 to August 2022. A total of 13 preclinical studies and 5 RCTs that included 212 animals and 260 patients were examined. The preclinical analysis showed that liver function indices [AST, SMD＝-1.41, P<0.0001; ALT, SMD＝-1.47, P<0.0001] were significantly improved in the soybean group compared with the model group, and fatty liver indicators [TG, SMD＝-0.78, P<0.0001; TC, SMD＝-1.38, P<0.0001] and oxidative stress indices [MDA, SMD＝-1.09, P<0.0001; SOD, SMD＝1.74, P=0.022] were improved in the soybean group. However, the five RCTs were not entirely consistent with the preclinical results, but the RCTs also confirmed the protective effect on the liver. The clinical RCTs showed that soybean has a significant effect on liver function, fatty liver, and oxidative stress indicators [ALT, SMD＝-0.42, P=0.006; TG, SMD＝-0.31, P=0.039; MDA, SMD＝-0.76, P=0.007]. The current meta-analysis combined preclinical and clinical studies and verified that soybean could protect the liver in NAFLD by regulating lipid metabolism and oxidative stress factors via the Akt/AMPK/PPARα signaling pathway. Soybean might be a promising therapeutic agent for treating nonalcoholic fatty liver disease.